2014
DOI: 10.1002/adom.201400347
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorescent, Photostable, Conjugated Polymer Dots with Amorphous, Glassy‐State, Coarsened Structure for Bioimaging

Abstract: have been developed for in vitro and in vivo bioimaging applications. CPDs have attracted considerable attention, because of their potential benefi ts such as relatively facile preparation, high fl uorescence (FL) emission quantum effi ciency, photostability, and low cytotoxicity. [ 2a ] However, CPDs still have some drawbacks, because of the characteristic electronic structures of conjugated polymers. First, in general, π-conjugated polymers have planar geometries and strong intermolecular interactions, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Nevertheless, quantum efficiencies hardly reach values over 50%. The introduction of specific moieties known to exhibit aggregation induced emission seems to be an attractive alternative solution, since those materials exhibit higher emission efficiencies when tight packing can be achieved [ 40 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, quantum efficiencies hardly reach values over 50%. The introduction of specific moieties known to exhibit aggregation induced emission seems to be an attractive alternative solution, since those materials exhibit higher emission efficiencies when tight packing can be achieved [ 40 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A very promising technique was introduced by Kim et al [ 50 ], who showed that the freezing of polydiphenylacetylene (PDPA, 23 and 24 ) into CPNPs in their relaxed state can lead to an extremely high PLQY of 76%. PDPA is an amorphous polymer and the effect of relaxed state freezing is very specific for this polymer of which the backbone is rigid, but highly twisted because of the steric hindrance caused by the phenyl side chains.…”
Section: Recent Developments In Bioimaging With Cpnpsmentioning
confidence: 99%
“…The AIE dots were prepared for conjugated polymers by using the nano-precipitation method as described previously [39,40]. The tetrahydrofuran stock solutions of PSMA (1 mg·mL −1 ) and DSA (0.5 mg·mL −1 ) were prepared, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[94][95][96][97] In a previous study, nanoprecipitation was examined using several PDPA derivatives and commercial CPs. 98 Among them, the p-C1-PDPA produced highly porous nanoparticles that dispersed very well in water. The polymer chains therein were either hydrodynamically or thermodynamically stable with the side phenyl rings being relaxed.…”
Section: Nanoprecipitation To Nanoparticlesmentioning
confidence: 99%
“…Additionally, the nanoparticles had higher photostability and lower cytotoxicity relative to conventional CPs. 98 The aqueous colloidal solution was suitable for bioimaging of live cells. Cellular uptake of the nanoparticles via endocytosis was observed.…”
Section: Detection Of Proteinsmentioning
confidence: 99%